THE ASSESSMENT OF MICROBIOLOGY OF THE BACTERIAL BIOFILM ADJACENT TO DIFFERENT TYPES OF THE MATERIALS USED FOR THE SEALING OF THE DENTAL OCCLUSAL FISSURES - Galina Pancu; Sorin Andrian; Gianina Iovan; Angela Gheorghe; Irina Nica; Claudiu Topoliceanu; Moldovanu Antonia; Nicoleta Tofan; Simona Stoleriu (Romanian Society of Oral Rehabilitation, 2017)
The incidence of the occlusal dental caries is still high, despite the numerous available preventive and therapeutic methods and materials. Further researches are requested to find the most effective preventive method. The aim of study was to assess during a year, by using Replica Test method, the retention degree and microbiology of the bacterial biofilm adjacent to the sealants performed by three types of materials: glass ionomer cement (group I), fluoride-releasing composite sealant (group II), and composite sealant without fluoride (group III). Results. For the group I, sealed with glass ionomer cement Replica Test results show low variations associated with high protective effect, due to the fluoride release. To the end of the research period, a slight increase of the bacterial biofilm activity was recorded. For the group II, sealed with a fluoride-releasing sealant, Replica Test results show, for the first 6 months, low variations associated with the high protective effect, due to the fluoride release. After 6 months, a slight increase of the bacterial biofilm activity the recorded, due to the decrease of the released fluoride ions level. For the group III, sealed with sealant without fluoride, Replica Test results show a progressive increase of the bacterial biofilm activity during the 12 months study period, more significant than to the other study groups. Conclusions. The results of our study show that all three sealing materials offer a low retentive surface associated with a reduction of the cariogenic bacterial biofilm adjacent to the sealings. The most significant reduction of the bacterial load was associated to the glass ionomer cement GC Fuji Triage, followed by flowable composite Fisurit FX and composite Fluid SDI Wave.